2012
DOI: 10.1002/alr.21032
|View full text |Cite
|
Sign up to set email alerts
|

Structured histopathology profiling of chronic rhinosinusitis in routine practice

Abstract: The diagnosis of ECRS has unique prognostic implications. Traditional features of the ECRS phenotype are not necessarily reliable markers for the presence of tissue eosinophilia. Serum eosinophilia may be a good surrogate marker of tissue eosinophilia but of limited use. The routine use of structured histopathology reporting in CRS is suggested, to allow for the diagnosis of ECRS and to identify other prognostic markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
282
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 197 publications
(302 citation statements)
references
References 44 publications
16
282
1
3
Order By: Relevance
“…[23] The association of ILC2s with tissue and blood eosinophilia further strengthen the argument for eosinophilic endotyping of CRS as part of routine practice as this more accurately reflects the underlying inflammatory disease process. [4] The study was limited due to the measurement of tissue eosinophilia in ordinal…”
Section: Accepted Articlementioning
confidence: 99%
“…[23] The association of ILC2s with tissue and blood eosinophilia further strengthen the argument for eosinophilic endotyping of CRS as part of routine practice as this more accurately reflects the underlying inflammatory disease process. [4] The study was limited due to the measurement of tissue eosinophilia in ordinal…”
Section: Accepted Articlementioning
confidence: 99%
“…1,4,29 Similar to several prior studies, we found no significant differences between CRS subtypes when comparing total scores on QOL instruments. 5,9,30,31 However, in this pilot study we did find differences in individual symptoms when CRS was subtyped by polyp or eosinophilic status (Figures 1–3). Although we acknowledge the potential for Type I error due to cohort size, patients in our study with CRSwNP had significantly more bothersome need to blow nose, more frequent nasal congestion, more severe difficulty breathing through nose, more severe nasal discharge, and decreased cough (Figures 1,2).…”
Section: Discussionmentioning
confidence: 53%
“…1,2,4–8 CRS without nasal polyps (CRSsNP) is more biologically heterogeneous with about 20% of patients demonstrating tissue eosinophilia. 5,9 …”
Section: Introductionmentioning
confidence: 99%
“…With advances in our understanding of the inflammatory processes, many investigators have recommended endotyping patients into eosinophilic versus noneosinophilic subsets using histopathological classification to improve the pathophysiology understanding and personalized management of CRSwNP [34,36 && ,40]. While many studies have tried to subclassify CRSwNP into eosinophilic and noneosinophilc subtypes, clear criteria for subclassifying eosinophilic and noneosinophilc remain elusive [48]. Most of the literature defines eosinophilic inflammation by examining the number or ratio of eosinophils in polyp tissues [49][50][51][52].…”
Section: Endotypes Of Chronic Rhinosinusitis: Eosinophilic Versus Nonmentioning
confidence: 99%